2018
DOI: 10.1097/nmd.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and Symptoms in Individuals at Clinical High Risk for Psychosis

Abstract: Individuals with psychotic symptoms often report low global self-esteem (GSE). However, it remains unclear whether the low GSE is linked to the presence of psychotic symptoms or it is present before the onset of psychosis. In addition, the specific subdomains of GSE in these populations are unknown. To address this question, we conducted a cross-sectional study comparing global and SE elements among individuals at clinical high risk for psychosis (CHR; n = 36), individuals with schizophrenia (SCZ; n = 43), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Six studies measured self-esteem, 3 used the Rosenberg Self-Esteem Scale, 30 , 63 , 64 2 studies used the Self-Esteem Rating Scale 62 (one used the short-form version 65 ) and one study used the Self-Perception Profile for Adults. 66 Across several studies, CHR individuals were found to have lower self-esteem relative to healthy controls, 30 , 62 , 64 , 66 and a longitudinal study reported that self-esteem in CHR did not significantly improve over time. 65 …”
Section: Resultsmentioning
confidence: 99%
“…Six studies measured self-esteem, 3 used the Rosenberg Self-Esteem Scale, 30 , 63 , 64 2 studies used the Self-Esteem Rating Scale 62 (one used the short-form version 65 ) and one study used the Self-Perception Profile for Adults. 66 Across several studies, CHR individuals were found to have lower self-esteem relative to healthy controls, 30 , 62 , 64 , 66 and a longitudinal study reported that self-esteem in CHR did not significantly improve over time. 65 …”
Section: Resultsmentioning
confidence: 99%
“…After discarding duplicates, 542 studies were identified in the initial search, 81 articles were read in full. After excluding studies that did not meet eligibility criteria, six papers were included in the meta-analysis (Atkinson et al, 2017;Benavides, Brucato, & Kimhy, 2018;Jongeneel et al, 2018;Park, Bang, Kim, Lee, & An, 2018;Pruessner et al, 2011;Shi et al, 2016). Study details are provided in Table 1.…”
Section: Search Strategymentioning
confidence: 99%
“…The most commonly used scale for assessment of self-esteem was the Rosenberg's Self-Esteem Scale [RSES: (Rosenberg, 1965)], used in three studies (Atkinson et al, 2017;Park et al, 2018;Shi et al, 2016), two studies (Jongeneel et al, 2018;Pruessner et al, 2011) employed the Self-Esteem Rating Scale [SERS; (Nugent & Thomas, 1993)] and one study (Benavides et al, 2018) used the Harter's Self-Perception Profile for Adults [SPPA; (Messer & Harter, 2012)]. The choice of measures is consistent with a recent review noting that the RSES and SPPA are among the most commonly used in published studies (Donnellan, Trzesniewski, & Robins, 2015).…”
Section: Self-esteem Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Por todos estos motivos, diferentes autores consideran que el entrenamiento en autoestima debería incluirse en los protocolos de tratamiento de la esquizofrenia (Benavides, Brucato & Kimhy, 2018;Costa et al, 2018), ya que una buena autoestima puede actuar como factor de protección en la evolución de la enfermedad (Benavides et al, 2018;Jongeneel et al, 2018).…”
Section: Introductionunclassified